DNA storage: research landscape and future prospects. Issue 6 (21st January 2020) - Dong, Yiming; Sun, Fajia; Ping, Zhi; Ouyang, Qi; Qian, Long
Abstract: The global demand for data storage is currently outpacing the world's storage capabilities. DNA, the carrier of natural genetic information, offers a stable, resource- and energy-efficient and sustainable data storage solution. In this review, we summarize the fundamental theory, research history, and technical challenges of DNA storage. From a quantitative perspective, we evaluate the prospect of DNA, and organic polymers in general, as a novel class of data storage medium.